Factor Affecting Wheat Seed Production and Associated Constraints in Kailali District, Nepal - Bist, Pratibha; Bhatt, Prashant; Bist, Naresh Singh; Kafle, Rojina (International Journal of Social Sciences and Management, 2021)
A seed is the most important input to increase wheat production. A seed is the biological basis of the world food security and, directly or indirectly supports the livelihood of every person on earth. To improve the productivity of wheat seed, it is important to adopt improved seed production technologies. Thus, the presented study was conducted with help of a well-structured questionnaire to assess the socio-demographic characteristics, economic status of producers, land &livestock holding, access to different agricultural services, drivers of seed production, market status and marketing of wheat seed, availability of different inputs, and constraints faced by seed producers during production as well as marketing. 60 formal and informal wheat seed producers were included in the survey. It was observed that the majority of wheat seed producers lacked services such as field inspection, roguing, cleaning, and processing. So, they do not acquire the best possible return from seed production. The number of middlemen involved in marketing of wheat seed is high, thus reducing price received by the farmers for their product. Due to lack of quality input, erratic rainfall, lack of technical support, lack of access to the market, the wheat seed production has not been carried out at its full potential in the study region. Int. J. Soc. Sc. Manage. Vol. 8, Issue-1: 299-305